Noninvasive Recording of True-to-Form Fetal ECG during the Third Trimester of Pregnancy - Istvan Peterfi; Lorand Kellenyi; Andras Szilagyi (Obstetrics and Gynecology International)
Objective. The aim of the study was to develop a complex electrophysiological measurement system (hardware and software) which uses the methods of electrophysiology and provides significant information about the intrauterine status of the fetus, intending to obtain true-to-form, morphologically evaluated fetal ECG from transabdominal maternal lead. Results. The present method contains many novel ideas that allow creating true-to-form noninvasive fetal ECG in the third trimester of the pregnancy in 80% of the cases. Such ideas are the telemetric data collection, the “cleanse” of the real time recording from the maternal ECG, and the use of the cardiotocograph (CTG) that allows identifying the fetal heart events. The advantage of this developed system is that it does not require any qualified staff, because both the extraction of the information from the abdominal recording and the processing of the data are automatic. Discussion. Although the idea of a noninvasive fetal electrocardiography is more than 100 years old still there is no simple, effective, and cheap method available that would enable an extensive use. This developed system can be used in the third trimester of the pregnancy efficiently. It can produce true-to-form fetal ECGs with amplitude less than 10 µV.